2001
DOI: 10.1128/jcm.39.12.4544-4548.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Penicillium marneffei Isolates from Thailand by Not I Macrorestriction and Pulsed-Field Gel Electrophoresis

Abstract: Penicillium marneffei is recognized as one of the most frequently detected opportunistic pathogens of AIDS patients in northern Thailand. We undertook a genomic epidemiology study of 64 P. marneffei isolates collected from immunosuppressed patients by pulsed-field gel electrophoresis (PFGE) with restriction enzyme NotI. Among the 69 isolates fingerprinted by PFGE, 17 were compared by HaeIII restriction endonuclease typing. The PFGE method demonstrated a higher degree of discriminatory power than restriction en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In contrast, Vanittanakom et al (47) detected only two HaeIII types among 46 isolates of P. marneffei. More recently, pulsed-field gel electrophoresis of NotI restriction endonuclease fragments was shown to be reproducible and highly discriminatory between isolates despite laborious sample preparation (46). The results of typing by PMM analysis in the present study of isolates ATCC 64102, 24100, 18224, and 64101 was consistent with the typing results obtained by NotI analysis of the same isolates by Vanittanakom et al (47); both methods showed these isolates to be unrelated.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, Vanittanakom et al (47) detected only two HaeIII types among 46 isolates of P. marneffei. More recently, pulsed-field gel electrophoresis of NotI restriction endonuclease fragments was shown to be reproducible and highly discriminatory between isolates despite laborious sample preparation (46). The results of typing by PMM analysis in the present study of isolates ATCC 64102, 24100, 18224, and 64101 was consistent with the typing results obtained by NotI analysis of the same isolates by Vanittanakom et al (47); both methods showed these isolates to be unrelated.…”
Section: Discussionsupporting
confidence: 81%
“…However, RAPD profiles have been shown to be unstable in Aspergillus fumigatus or too sensitive to reaction conditions (4,27). Macrorestriction digestion profiles of NotI restriction fragments resolved by pulsed-field gel electrophoresis for 69 P. marneffei isolates obtained from AIDS patients in Thailand detected 54 patterns (46). Although it provided good discriminatory power, NotI restriction fragment length polymorphism analysis was reported to lack concordance with HaeIII analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two HaeIII types for 46 isolates were reported (53). Randomly amplified polymorphic DNA and macrorestriction profiles have been utilized for typing, but these methods are difficult to reproduce or it is difficult to compare results between laboratories (23,26,51). Recently, microsatellite markers have been shown to provide high degree of discriminatory power and reproducibility for typing P. marneffei isolates (15,16,17,21,30).…”
Section: Discussionmentioning
confidence: 99%
“…Trewatcharegon et al have used pulsed-field gel electrophoresis (PFGE) and Fisher et al have used multilocus microsatellite typing for typing P. marneffei (13,14,36). However, due to experimental variations, PFGE patterns are difficult to compare among different laboratories.…”
mentioning
confidence: 99%